Association of Adherence Support and Outreach Services with Total Attrition, Loss to Follow-Up, and Death among ART Patients in Sub-Saharan Africa - Lamb, Matthew R.; El-Sadr, Wafaa M.; Geng, Elvin; Nash, Denis (PLOS ONE, 2012)
Background Loss to follow-up (LTF) after antiretroviral therapy (ART) initiation is common in HIV clinics. We examined the effect of availability of adherence support and active patient outreach services on patient attrition following ART initiation. Methods and Findings This ecologic study examined clinic attrition rates (total attrition, LTF, and death) among 232,389 patients initiating ART at 349 clinics during 2004–2008 in 10 sub-Saharan African countries, and cohort attrition (proportion retained at 6 and 12 months after ART initiation) among a subset of patients with follow-up information (n = 83,389). Log-linear regression compared mean rates of attrition, LTF, and death between clinics with and without adherence support and outreach services. Cumulative attrition, LTF, and death rates were 14.2, 9.2, and 4.9 per 100 person-years on ART, respectively. In multivariate analyses, clinic availability of >2 adherence support services was marginally associated with lower attrition rates (RRadj = 0.59, 95%CI: 0.35–1.0). Clinics with availability of counseling services (RRadj = 0.62, 95%CI: 0.42–0.92), educational materials (RRadj = 0.73, 95%CI: 0.63–0.85), reminder tools (RRadj = 0.79, 95%CI: 0.64–0.97), and food rations (RRadj = 0.72, 95%CI: 0.58–0.90) had significantly lower attrition, with similar results observed for LTF. Outreach services were not significantly associated with attrition. In cohort analyses, attrition was significantly lower at clinics offering >2 adherence support services (RRadj,6m = 0.84, 95%CI: 0.73–0.96), dedicated pharmacy services (RRadj,6m = 0.78, 95%CI: 0.69–0.90), and active patient outreach (RRadj,6m = 0.85, 95%CI: 0.73–0.99). Availability of food rations was marginally associated with increased retention at 6 (RRadj,6m = 0.82, 95%CI: 0.64–1.05) but not 12 months (RRadj,12m = 0.98, 95%CI: 0.78–1.21). Conclusions Availability of adherence support services, active patient outreach and food rations at HIV care clinics may improve retention following ART initiation.